Does Patient-Reported Olfactory Improvement Correlate with Quality of Life and Polyp Size Reduction in Patients with CRSwNP Treated with Dupilumab? - Brian Hernández-Martín; Miriam del Carmen Marrero-Ramos; María Soledad Cabrera-Ramírez; Jesús Javier Benítez-Rosario; Carmen Delia Dávila-Quintana; María Sandra Domínguez-Sosa (Medicines, 2026)
Background: Olfactory dysfunction (OD) is a key symptom of chronic rhinosinusitis with nasal polyps (CRSwNP). Dupilumab improves clinical outcomes, including patient-reported olfactory function. This study aimed to analyze correlations between patient-reported olfactory improvement, quality of life, and endoscopic outcomes in patients treated with dupilumab. Methods: A real-life, single-center retrospective study included 35 patients with severe, uncontrolled CRSwNP treated with dupilumab. Patient-reported olfactory function was assessed using a visual analog scale (VAS-olfaction), quality of life with the Sinonasal Outcome Test-22 (SNOT-22), and polyp size with the Nasal Polyp Score (NPS) at baseline, 6 months, and 12 months. Changes from baseline were analyzed using the Wilcoxon signed-rank test, whereas correlations were evaluated using Spearman’s rank correlation coefficient. Results: Dupilumab was associated with significant improvements in patient-reported olfactory function, quality of life, and polyp size at 6 and 12 months. Improvements in VAS-olfaction correlated significantly with SNOT-22 at 6 months (p = 0.035) and 12 months (p = 0.024). In a sensitivity analysis excluding the smell/taste item from the SNOT-22, these correlations were attenuated and no longer reached statistical significance. No significant correlation was observed between patient-reported olfactory improvement and NPS. Conclusions: Patient-reported olfactory improvement correlated with quality of life but not with reductions in global polyp burden. These findings suggest that this improvement may not be fully explained by changes in polyp size alone.